2009
DOI: 10.1139/l09-067
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of sharp-crested weir flows

Abstract: The sharp-crested weir in a rectangular open channel can be used as a simple and accurate device for flow measurement and control in open channels. However, in the past, the solution to this problem was found mainly on the basis of experimental data or through the development of simplified theoretical expressions. In the present study, k-ε turbulence model is applied to obtain the flow parameters such as pressure head distributions, velocity distributions, and water surface profiles. The predictions of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…The results of the simulations were validated using experimental data of surface profiles, distributions of velocities and pressure heads. Qu et al (2009) concluded that the velocity and pressure head distributions in the nappe region were in very good agreement with the experimental results. The surface profiles of the simulation also agreed with the experimental profiles.…”
Section: Literature Surveysupporting
confidence: 72%
See 2 more Smart Citations
“…The results of the simulations were validated using experimental data of surface profiles, distributions of velocities and pressure heads. Qu et al (2009) concluded that the velocity and pressure head distributions in the nappe region were in very good agreement with the experimental results. The surface profiles of the simulation also agreed with the experimental profiles.…”
Section: Literature Surveysupporting
confidence: 72%
“…Similarly, Qu et al (2009) reported the two-dimensional (2D) numerical simulation of sharp-crested weir flows in a rectangular open channel. The standard two-equation Wilcox k-ø turbulence model was adopted for the numerical simulation of turbulence and, again, the VOF method was utilised to capture the free surface between air and water.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, a new research work has appeared [16], the only one (to the knowledge of the author) that has published numerical results on sharp-crested weir flow. In [16] the two-dimensional incompressible Navier-Stokes equations have been solved using the volume of fluid (VOF) method of Hirt and Nichols [11].…”
Section: Introductionmentioning
confidence: 99%
“…Modelling of flow over sharp weir and validation has been carried on by numerous investigations. A good agreement had found between simulation of weir flow and carried a comparison of flow properties such as pressure head, distribution of velocity, and water surface profiles with that of experimental data by employing k-ε turbulence model [1]. Following the method of Zhao and Tai for finite volume numerical hybrid level discretizations, Lv et al [2] were able to study the flow over sharp and broad weirs for validation of that numerical schemes.…”
Section: Introductionmentioning
confidence: 83%